2013
DOI: 10.1002/jsfa.6019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of starch phosphorylases in barley grains

Abstract: Two starch phosphorylase activities were identified and characterized in barley grains, and shown to be present during starch synthesis. However, their role in starch synthesis still remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The precise role for SP in starch biosynthesis is not at all clear. SP is present in all tissues synthesizing starch, and its expression in developing endosperm tissue of a number of cereals is closely correlated with periods of active starch accumulation [299,353,354]. Genetic studies in rice indicate a role for SP in starch accumulation.…”
Section: Starch Phosphorylasementioning
confidence: 99%
See 1 more Smart Citation
“…The precise role for SP in starch biosynthesis is not at all clear. SP is present in all tissues synthesizing starch, and its expression in developing endosperm tissue of a number of cereals is closely correlated with periods of active starch accumulation [299,353,354]. Genetic studies in rice indicate a role for SP in starch accumulation.…”
Section: Starch Phosphorylasementioning
confidence: 99%
“…Genetic studies in rice indicate a role for SP in starch accumulation. Rice mutants lacking Pho1 show shrunken endosperm and altered starch granule characteristics when plants were grown at low temperature, possibly indicating a role for SP in starch accumulation under different environmental conditions [355], although a down-regulation of Pho1 expression in barley had no major effects on starch biosynthesis [354]. In addition, studies of SP from other plant tissues show no compelling evidence for a role in transitory starch turnover [356,357].…”
Section: Starch Phosphorylasementioning
confidence: 99%
“…Several classes of enzymes are involved in starch biosynthesis, including ADP-glucose pyro-phosphorylase (AGPase), granule-bound starch synthase (GBSS), soluble starch synthase (SSS), starch branching enzyme (SBE), starch debranching enzyme(DBE), and plastidial starch phosphorylase (Pho1), moreover GBSS, SSS, SBE and DBE have multiple isoforms [4, 812]. SBE (EC 2.4.1.18), which is a glucosyl transferase that catalyzes the formation of the α-1, 6-linkages of amylopectin, introduces branches in starch chains and thus plays a vital role in amylopectin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently however, it was shown that a reduction of Hv Pho1 protein levels in barley grains to under 30% of their normal value did not lead to any visible starch phenotype [52]. Nevertheless, less than 30% Hv Pho1 activity may be sufficient to drive production of primer molecules acting as initiator-glucans.…”
Section: Discussionmentioning
confidence: 99%